Functional comparision of the sub-Mediterranean illyrian meadows from two distinctive geological substrates - Pipenbaher, Nataša (Annales. Series historia naturalis, 2008)
In this paper, floristic and functional approaches to the classification of different types of sub-Mediterranean illyrian grasslands of the association Danthonio-Scorzoneretum villose lalliance Scorzonerion villosae, order Scorzoneretalia villosae, class Festuco-Brometea) are compared. The data set includes table with 30 relevés from SW Slovenia, sampled in two contrasting geological bedrocks - flysch and limestone - and matrix with 18 treits determined for 119 plant species. We also tested an impact of different geological bedrock on the relative proportions of C-S-R plant strategies in the relevés. With DCA ordinetion, relevés from limestone and flysch were clearly divided in two groups. First DCA axis suggested a gradient of soil humidity and pH. On the basis of selected traits, 5 Plant Functional Types were clustered and interpreted with Twinspan analysis. PCA ordination of relevés on the basis of plant functional traits revealed that samples from limestone could be separated from those taken on flysch substrate also with functional approach. Reievés from limestone tend to have bigger shares of species, which propagate by seed and vegetatively, and competitors and herbs. Nevertheless, it could be concluded that there are no major functional differences between meadows from both geological substrates. The positions of all relevés in standard C-S-R temary diagram showed that that the relative proportions of C-S-R functional types were not influenced by different geological bedrock.
Keywords: botanika; Rhododendron-Park Bremen; severni Jadran; suhi travniki; travišča; vegetacija